EFFECTIVENESS OF BLENDED LEARNING BASIC LIFE SUPPORT (BLS) TRAINING ON KNOWLEDGE OF NURSING STUDENTS - Mokhtar Jamil; Merisdawati Merisdawati (Jurnal Kesehatan Mesencephalon, 2022)
Cardiac arrest is a sudden loss of heart function, the time of its occurrence is unpredictable and very quickly. Cardiac arrest events require a Chain Of Survival action, one of them is ability to do Basic Life Support (BLS) Skill. The number of nursing students were quite large, most of their time was spent in the community, giving them the opportunity to act as first responders in OHCA cases in the community. The purpose of this study was to determine the effect of BLS training on increasing knowledge first aid in cardiac arrest. The research design was pre-experimental with a sample consist of 229 students using a total sampling technique. The variables studied were knowledge before and after BLS training. Knowledge was assessed using a questionnaire. Statistical test using Wilcoxon Sign Rank Test. The results showed that the average pretest was 43.41 and the post-test average was 77.24. The value of p = 0.000 (<0.05) which means that there is an effect of Basic Life Support (BLS) training on knowledge of cardiac arrest first aid. Several factors behind the results were exposure to initial information, module provision and video and simulation methods. The research expected to be developed by providing a control group and cross sectional design.Keywords: Basic Life Support, Cardiac Arrest, Student